Study on designing the feedback loop control of buck converter - Khan, Md. Abdul Mobin; Rahman, Asifur; Hoque, Md. Rezuanul (BRAC University, 2017)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2016.